Relationship between plasma inflammatory markers and plaque fibrous cap thickness determined by intravascular optical coherence tomography. Issue 3 (28th October 2009) - Li, Q-X; Fu, Q-Q; Shi, S-W; Wang, Y-F; Xie, J-J; Yu, X; Cheng, X; Liao, Y-H
Abstract : Objective: The purpose of this study was to evaluate the relationship between human plaque fibrous cap thickness detected by intravascular optical coherence tomography (OCT) and the plasma levels of inflammatory factors in patients with coronary artery disease (CAD). Methods and Results: OCT was used to measure the fibrous cap thickness of coronary artery atherosclerotic plaques in patients with acute myocardial infarction (AMI), unstable angina pectoris (UAP) and stable angina pectoris (SAP). Plasma levels of inflammatory factors including highly sensitive C-reactive protein (hs-CRP), IL-18 and tumour necrosis factor alpha (TNFα) were detected by ELISA, and peripheral white blood cell (WBC) counts were performed. The results demonstrated that the plasma levels of inflammatory factors and WBC count were correlated inversely with fibrous cap thickness (r = −0.775 for hs-CRP, r = −0.593 for IL-18, r = −0.60 for TNFα and r = −0.356 for WBC count). Patients with cap thickness less than 65 μm (defined to be thin cap fibroatheromas; TCFA) had higher plasma levels of inflammatory factors as well as WBC counts than those with thicker fibrous caps. Receiver operator characteristic (ROC) curves for hs-CRP, IL-18, TNFα and WBC count, which displayed the capability of prediction about TCFA, showed the area under the curves were 0.95, 0.86, 0.79 and 0.70 (p<0.05), respectively. ROC curve analysis confirmed that an hs-CRP cut-off at 1.66 mg/l would detect TCFA with a sensitivity of 96% and a specificity of 90%, and was the strongest independent predictor of TCFA. Conclusion: There is an inverse linear correlation between fibrous cap thickness and plasma levels of inflammatory markers. The plasma hs-CRP concentration is the strongest independent predictor of TCFA.